Determination of Leuprolide–Fatty Acid Conjugate in Rat Plasma Using LC-MS/MS and Its Pharmacokinetics after Subcutaneous Administration in Rats - Seong, Gi Sang; Seo, Seong Wook; Cho, Ji Young; Lee, Kye Wan; Lee, Beom Jin; Yoon, In Soo; Jin, Hyo Eon (Molecules, 2022)
Leuprolide is a synthetic nonapeptide drug (pyroGlu-His-Trp-Ser-Tyr-d-Leu-Leu-Arg-Pro-NHEt) that acts as a gonadotropin-releasing hormone agonist. The continuous administration of therapeutic doses of leuprolide inhibits gonadotropin secretion, which is used in androgen-deprivation therapy for the treatment of advanced prostate cancer, central precocious puberty, endometriosis, uterine fibroids, and other sex-hormone-related conditions. To improve the pharmacokinetic properties of peptide drugs, a fatty acid was conjugated with leuprolide for long-term action. In this study, we developed a simple ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method for the simultaneous determination of leuprolide and leuprolide–oleic acid conjugate (LOC) levels. The developed method was validated in terms of linearity, precision, accuracy, recovery, matrix effect, and stability according to the US Food and Drug Administration guidelines, and the parameters were within acceptable limits. Subsequently, the pharmacokinetics of leuprolide and LOCs were evaluated. In vivo rat subcutaneous studies revealed that conjugation with fatty acids significantly altered the pharmacokinetics of leuprolide. After the subcutaneous administration of fatty-acid-conjugated leuprolide, the mean absorption time and half-life were prolonged. To the best of our knowledge, this is the first study showing the effects of fatty acid conjugates on the pharmacokinetics of leuprolide using a newly developed UPLC-MS/MS method for the simultaneous quantification of leuprolide and LOCs.
Keywords: Androgen Antagonists; Animals; Chromatography, High Pressure Liquid; Chromatography, Liquid; Fatty Acids; Female; Humans; Leuprolide; Male; Prostatic Neoplasms; Rats; Tandem Mass Spectrometry; comparative pharmacokinetics; fatty-acid-conjugated leuprolide; leuprolide; peptide; UPLC-MS/MS